Design and Development of a Web-Based Complaints Management System at Syiah Kuala University Integrated Laboratory - Mutiawani, Viska; Hafist, Pilar Al; Dawood, Rahmad (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Complaint handling is essential to Syiah Kuala University’s Integrated Laboratory Technical Management Unit (ILTMU) services. However, manual complaint handling at ILTMU requires more time and energy and increases the staff workload. Complaint handling is necessary to continuously improve the performance efficiency and service quality provided by ILTMU. Therefore, to solve the problem of handling complaints manually, this research intends to design and develop a web-based complaint management system at ILTMU of Syiah Kuala University. The proposed system uses the Goal-Directed Design method, while the development process follows Scrum. The system was developed using Flask and some services from the Google Cloud Platform, namely, the Google App Engine and Google Cloud Datastore. The system is divided into four unique user groups. Each has access privileges and responsibilities: operators, Management, Follow-up, and Customers. Each of these user groups has its distinctive features. The entire features of this application were tested using both Black Box and White Box testing. All system functions were successfully executed using the Black Box testing technique. Meanwhile, the White Box testing returned a value of 100% passed, indicating that the function being tested is error-free. A usability test was conducted with 20 respondents representing each user group using the USE Questionnaire on a 7-point Likert scale. The usability test results gave an overall average value of 6.13, which suggests that people have a positive attitude toward the system and that it is practical, easy to use, easy to learn, and satisfying.